Implementation of The Cooperative Learning Model in Islamic Cultural History Lessons at Madrasah Aliyah Roudlotul Khuffadz - Syaifulloh Alwi Zamzami; Muhammad Satir; Sella Nofriska Sudrimo (Universitas Nurul Jadid, 2026)
This study aims to analyze the implementation of the cooperative learning model in the subject of Islamic Cultural History (ISH) in class XI of Madrasah Aliyah Roudlotul Khuffadz, and to identify opportunities and obstacles in its implementation. This study uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation with research subjects consisting of the principal of the madrasah, ISH teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using triangulation techniques to ensure data validity. The results of the study indicate that the implementation of the cooperative learning model has run quite well and is able to increase the activeness, understanding, and social interaction of students in learning. This model also provides opportunities to develop cooperation, communication, and student responsibility. However, there are still obstacles such as differences in student abilities, unequal participation in groups, limited learning time, and suboptimal classroom management. The conclusion of this study shows that cooperative learning is an effective learning model, but requires good management to provide maximum results in the learning process.